Malignancies after heart transplantation: incidence, risk factors, and effects of calcineurin inhibitor withdrawal - Dösch, Andreas; Müller, Susanne; Konstandin, Mathias; Celik, Sultan; Kristen, Arnt; Frankenstein, Lutz; Ehlermann, Philipp; Sack, Falk-Udo; Katus, Hugo; Dengler, Thomas (Transplantation proceedings, 2010)
The objectives of the present study were to evaluate the incidence of malignancies and to describe the effects of immunosuppression on survival and recurrence of malignancies after heart transplantation (HTX). Data were analyzed in 211 cardiac allograft recipients, in whom HTX was performed between 1989 and 2005. All of these patients survived for more than 2 years after HTX and received induction therapy with antithymocyte globulin (RATG) guided by T-cell monitoring since 1994. An immunosuppressive regimen consisting of cyclosporine A (CsA) combined with azathioprine was followed by CsA and mycophenolate mofetil (MMF) in 2001; mammalian target of rapamycin (mTOR) inhibitors (everolimus/sirolimus) were used since 2003. Mean patient age at HTX was 51.4 ± 10.5 years; mean follow-up time after HTX 9.2 ± 4.7 years. Overall incidence of neoplasias was 30.8%. Individual risk factors associated with a higher risk of malignancy after HTX were higher age at transplantation (P = .003), male gender (P = .005) and ischemic cardiomyopathy before HTX (P = .04). Administration of azathioprine (P < .0001) or a calcineurin inhibitor (CNI) (P = .02) for more than 1 year was associated with development of malignancy, whereas significantly fewer malignancies were noticed in patients receiving an mTOR-inhibitor (P < .0001). Kaplan-Meier analysis demonstrated a strong statistical trend toward an improved survival in patients with a noncutaneous neoplasia switched to a CNI-free protocol (P = .05). This study demonstrated the impact of a variety of individual risk factors and immunosuppressive drugs on development of malignancy after HTX. Markedly fewer patients with noncutaneous malignancies died after switch to a CNI-free regimen, not quite reaching statistical significance by Kaplan-Meier analysis, however.